Mechanical ventilation at the time of heart transplantation and associations with clinical outcomes. Issue 8 (14th August 2021) - Miller, P Elliott; Mullan, Clancy W; Chouairi, Fouad; Sen, Sounok; Clark, Katherine A; Reinhardt, Samuel; Fuery, Michael; Anwer, Muhammad; Geirsson, Arnar; Formica, Richard; Rogers, Joseph G; Desai, Nihar R; et al.
Abstract: Aims: The impact of mechanical ventilation (MV) at the time of heart transplantation is not well understood. In addition, MV was recently removed as a criterion from the new US heart transplantation allocation system. We sought to assess for the association between MV at transplantation and 1-year mortality. Methods and results: We utilized the United Network for Organ Sharing database and included all adult, single organ heart transplantations from 1990 to 2019. We utilized multivariable logistic regression adjusting for demographics, comorbidities, and markers of clinical acuity. We identified 60 980 patients who underwent heart transplantation, 2.4% ( n = 1431) of which required MV at transplantation. Ventilated patients were more likely to require temporary mechanical support, previous dialysis, and had a shorter median waitlist time (21 vs. 95 days, P < 0.001). At 1 year, the mortality was 33.7% ( n = 484) for ventilated patients and 11.7% ( n = 6967) for those not ventilated at the time of transplantation (log-rank P < 0.001). After multivariable adjustment, patients requiring MV continued to have a substantially higher 90-day [odds ratio (OR) 3.20, 95% confidence interval (CI): 2.79–3.66, P < 0.001] and 1-year mortality (OR 2.67, 95% CI: 2.36–3.03, P < 0.001). For those that survived to 90 days, the adjusted mortality at 1 year continued to be higher (OR 1.48, 95% CI: 1.16–1.89, P = 0.002). Conclusion: We found a strong association between the presence of MV at heart transplantation and 90-day and 1-year mortality. Future studies are needed to identify which patients requiring MV have reasonable outcomes, and which are associated with substantially poorer outcomes. Graphical Abstract: